Frontispiece: Stereoelectronic Chameleons: The Donor–Acceptor Dichotomy of Functional Groups. Issue 14 (8th March 2017) - Vatsadze, Sergey Z.; Loginova, Yulia D.; dos Passos Gomes, Gabriel; Alabugin, Igor V.
Abstract : Chameleonic Behavior The traditional view of common functional groups as either donors or acceptors is challenged by stereoelectronic thinking. In the Review onpage 3225 ff., S. Z. Vatsadze, I. V. Alabugin et al. discuss situations in which the donor–acceptor properties of substituents and, hence, chemical reactivity can be inverted as a function of their orientation in space with respect to the rest of a molecule. They discuss conformational, translocational and supramolecular "stereoelectronic chameleons" with focus on the situations in which the stereoelectronic "umpolung" unlocks useful ways of thinking about chemical reactivity and opens new doors for reaction design.